The role of practicing physical education and sports in improving the motor aspect of students - kaarouche, nouari (sports creativity, 2024)
The study aimes to determine the role of physical education and sports in improving the motor aspect of students. A questionnaire form was used and a sample of 36 education teachers was selected randomly. Validity and reliability were also calculated for a sample of 06 individuals. Among the most important results reached: Practicing physical education and sports helps students. On accuracy in motor performance